Controllable fabrication of nitrogen-deficient graphitic carbon nitride/magnetic ferric oxide and N2 photofixation on the active sites of surface defects. (January 2022) - Rong, Xinshan; Zhang, Shixian; Rong, Jian; Wei, Jing; Qiu, Xuchun; Wu, Zhiren
Highlights: Z-scheme GCNx/FO photocatalyst was obtained by one-step calcination method. Amount of surface nitrogen defect and the phase of ferric oxide could be tuned easily. Introduction of nitrogen defect improved the N2 adsorption and activation effectively. Abstract: Z-scheme nitrogen-deficient graphitic carbon nitride/ferric oxide (GCNx /FO) photocatalysts were obtained by a one-step calcination method. The number of nitrogen defects was tuned by the application of KOH, while the ferric oxide phase and magnetism was controlled by the usage of ferrous oxalate. Interconversion between the hematite (α) and maghemite (γ) phases of Fe2 O3 was analyzed by X-ray diffraction, and magnetism of the GCNx -0.1/FO products provided via vibrating sample magnetometer test. The introduction of nitrogen defects narrowed the bandgap and extended the spectral range of light absorption while improving the ability to capture and activate N2 effectively. Surface defects were employed as active sites, and the ammonia generation concentration reached approximately 69.7 μmol/L/h by N2 photofixation under visible light. Due to their ease of synthesis and tuning, high photocatalytic activity, convenient and rapid collection for reuse, and excellent stability, GCNx /FO composited photocatalysts possess vast potential for use in clean ammonia production. Graphical abstract: Z-scheme nitrogen deficient graphitic carbon nitride/ferric oxide (GCNx /FO) photocatalyst was obtained by one-step calcination method, and which was explored for an energy-efficient and environmentally friendly nitrogen fixation process. Image, graphical abstract